2012
DOI: 10.1007/s00428-012-1276-1
|View full text |Cite
|
Sign up to set email alerts
|

Stromal p16 expression differentiates endometrial polyp from endometrial hyperplasia

Abstract: Endometrial polyps are very common benign endometrial lesions, but their pathogenesis is poorly understood, except for a few studies indicating the possibility of benign stromal neoplasm. Although the histopathological diagnosis of endometrial polyp on a surgical specimen is straightforward, it is often difficult to differentiate endometrial polyp from endometrial hyperplasia on a biopsy or curettage specimen. Presently, there is no immunohistochemical marker helpful in this differential diagnosis. In this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
27
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 25 publications
3
27
1
1
Order By: Relevance
“…In addition, both EC and AH/EIN exhibited significantly higher stromal p16 expression levels compared with hyperplasia without atypia or endometrial polyp. This result was opposite to that of the previous study by Moritani et al [28]. We attribute these differences to the following two reasons.…”
Section: Discussioncontrasting
confidence: 96%
See 3 more Smart Citations
“…In addition, both EC and AH/EIN exhibited significantly higher stromal p16 expression levels compared with hyperplasia without atypia or endometrial polyp. This result was opposite to that of the previous study by Moritani et al [28]. We attribute these differences to the following two reasons.…”
Section: Discussioncontrasting
confidence: 96%
“…We found one previous study reporting stromal p16 expression in endometrial neoplastic lesions [28]. For 80.0% (28/35) of endometrial polyp cases, p16 immunoreactivity with moderate or greater intensity was observed in fibrous stroma, and 1 (3.0%; 1/33) case of endometrial hyperplasia showed weak p16 expression; however, none of the endometrial carcinoma cases (0.0%; 0/23) showed stromal p16 expression.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…On this basis, we proposed that the accumulation of senescent cells in EC tissue suppresses the progression of cancer. In accordance with previous reports that p16 INK4a expression is upregulated in endometrial polyps compared to endometrial hyperplasia due to the p16-induced cellr senescence (23), our functional investigations indicated that p16…”
Section: Discussionsupporting
confidence: 93%